Analisis Penerapan Nilai-Nilai Qur'ani dalam Pembentukan Literasi Digital Remaja Muslim di Era Media Sosial - Dede Sarim; Achmad Junaedi Sitika; Alam Tarlam; Cucu Khoeriyah (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
The implementation of digital literacy based on Qur'anic values at SMPIT Buah Hati aims to shape students' Islamic character in using social media. This research was carried out to explore the impact of applying Qur'anic values in improving students' critical and ethical attitudes towards information circulating on social media. The research method used is a qualitative method with a case study approach. Data collection techniques are carried out through observation, interviews and documentation. The collected data was analyzed using qualitative descriptive analysis techniques to interpret changes in student attitudes and behavior. The research results show that the application of digital literacy based on Qur'anic values has a positive influence on students' attitudes in using social media. Students become more selective in choosing content, respect differences of opinion, and are responsible in disseminating information. They are also more critical of content that conflicts with Islamic teachings and are proactive in maintaining a healthy digital environment. Apart from that, the teacher's role as a facilitator and guide is very important in providing real examples and encouraging students to think critically and apply Qur'anic values in the virtual world. The implication of this research is the importance of integrating Qur'anic values in digital literacy programs in schools to form students' characters who are responsible, ethical and wise in using technology. This program can be used as a model for other Islamic schools in equipping students to face challenges in the digital world.